The Effect of Perceived Ease of Use, Usefulness of Qris on Impulsive Consumptive Behavior with Digital Financial Literacy Moderation - Rifani, Milsa; Rizal Putri, Vidiyanna; Maju Simatupang, Batara; Pracoyo, Antyo (Dinasti Publisher, 2026)
This study aims to analyze the influence of perceived ease of use and perceived usefulness of QRIS on consumptive behavior, with impulsive buying as a mediating variable and digital financial literacy as a moderating variable. Using a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS) on 93 bank employees in Jakarta, the findings indicate that perceived ease of use decreases consumptive behavior but increases impulsive buying, while perceived usefulness significantly affects impulsive buying but does not directly influence consumptive behavior. Impulsive buying is shown to increase consumptive behavior and serves as a partial mediator in the relationship between perceived ease of use and consumptive behavior, and as a full mediator in the relationship between perceived usefulness and consumptive behavior. Moreover, digital financial literacy plays a moderating role by weakening the effect of impulsive buying on consumptive behavior, thereby helping to control excessive consumption tendencies and contributing to a deeper understanding of the behavioral implications of digital payment technologies.